A comparative study on modified epoxy and glycidyl carbamate coatings for corrosion and fouling prevention. Issue 2 (June 2015) - Dhanapal, Duraibabu; Rebheka, Gowripriya; Palanivel, Saravanan; Srinivasan, Ananda Kumar
Abstract : The objective of the study focuses on the development and characterization of modified epoxy (ME) and glycidyl carbamate (GC) coatings. The coatings were applied on mild steel specimens by bar coated to a thickness of 80 µm using Aradur 140 (polyamidoimidazoline) curing agent. ME and GC coatings were characterized by means of Fourier transform infrared and nuclear magnetic resonance spectral studies to ascertain their structure. The corrosion- and fouling-resistant behavior of these coatings in comparison with a commercially available paint was determined by potentiodynamic polarization, electrochemical impedance spectroscopy (EIS), scanning electron microscopy and antifouling studies. These coatings appear to be both corrosion and fouling resistant.